2007
DOI: 10.1525/jer.2007.2.3.23
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Committee Experience with Emergency Exception from Informed Consent Protocols

Abstract: SINCE 1996, U.S. FEDERAL REGULATIONS allow research without informed consent to study emergency conditions, if there is currently no satisfactory treatment for the condition, no time to obtain advance consent from the patient or representative, and if there is community involvement through a public disclosure and community consultation process. REB experiences since then are unknown. We surveyed REB chairpersons at the 126 United States medical schools to quantify reviewed protocols and identify attitudes abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In the United States, regulators experienced protocols including waived consent as more complex and time consuming to review [ 78 , 79 ], with one study reporting a mean time of 8.8 h, compared with 2.3 for studies not conducted under EFIC [ 79 ]. A key challenge in applying the law involved determining what constitutes adequate community consultation and public notification [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, regulators experienced protocols including waived consent as more complex and time consuming to review [ 78 , 79 ], with one study reporting a mean time of 8.8 h, compared with 2.3 for studies not conducted under EFIC [ 79 ]. A key challenge in applying the law involved determining what constitutes adequate community consultation and public notification [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, many IRBs at the local level lack sufficient experience and expertise in research involving exception from informed consent. A recent survey of IRB chairpersons31 found that 25 of 52 had reviewed such a study, while 42 felt prepared to do so. Even if an institution had previous experience with exception from informed consent, many IRB members may not feel adequately trained to review these protocols 32…”
Section: Informed Consentmentioning
confidence: 99%
“…Future studies correlating IRB members’, EMS providers’, and researchers’ perspectives on community consultation would be very valuable. Currently, very limited data exist regarding these important stakeholders’ views of community consultation (1214). …”
Section: Discussionmentioning
confidence: 99%